Expression in Pichia pastoris of human antibody fragments that neutralize venoms of Mexican scorpions. (February 2023) - Gómez-Ramírez, Ilse V.; Corrales-García, Ligia Luz; Possani, Lourival D.; Riaño-Umbarila, Lidia; Becerril, Baltazar
Abstract: The methylotrophic yeast Pichia pastoris has been one of the most widely used organisms in recent years as an expression system for a wide variety of recombinant proteins with therapeutic potential. Its popularity as an alternative system to Escherichia coli is mainly due to the easy genetic manipulation and the ability to produce high levels of heterologous proteins, either intracellularly or extracellularly. Being a eukaryotic organism, P. pastoris carries out post-translational modifications that allow it to produce soluble and correctly folded recombinant proteins. This work, evaluated the expression capacity in P. pastoris of two single-chain variable fragments (scFvs) of human origin, 10FG2 and LR. These scFvs were previously obtained by directed evolution against scorpion venom toxins and are able to neutralize different toxins and venoms of Mexican species. The yield obtained in P. pastoris was higher than that obtained in bacterial periplasm ( E. coli), and most importantly, biochemical and functional properties were not modified. These results confirm that P. pastoris yeast can be a good expression system for the production of antibody fragments of a new recombinant antivenom. Graphical abstract: Image 1 Highlights: Two antibody fragments of human origin were successfully expressed in Pichia pastoris . Higher expression yields of scFvs LR and 10FG2 as compared to E. coli were obtained. Biochemical properties of scFvs LR and 10FG2 expressed in Pichia pastoris did not change. The scFvs LR and 10FG2 maintain the ability to neutralize scorpion venoms.